Training of Physical Therapists to Deliver Individualized Biopsychosocial Interventions to Treat Musculoskeletal Pain Conditions: A Scoping Review. Issue 10 (30th July 2021) - Simpson, Phoebe; Holopainen, Riikka; Schütze, Robert; O'Sullivan, Peter; Smith, Anne; Linton, Steven J; Nicholas, Michael; Kent, Peter
Abstract: Objective: Current guidelines recommend management of musculoskeletal pain conditions from a biopsychosocial approach; however, biopsychosocial interventions delivered by physical therapists vary considerably in effectiveness. It is unknown whether the differences are explained by the intervention itself, the training and/or competency of physical therapists delivering the intervention, or fidelity of the intervention. The aim was to investigate and map the training, competency assessments, and fidelity checking of individualized biopsychosocial interventions delivered by physical therapists to treat musculoskeletal pain conditions. Methods: A scoping review methodology was employed, using Arksey and O'Malley's framework. Seven electronic databases were searched between January and March 2019, with a bridge search completed in January 2020. Full-text peer-reviewed articles, with an individualized biopsychosocial intervention were considered, and 35 studies were included. Results: Reporting overall was sparse and highly variable. There was a broad spectrum of training. More sophisticated training involved workshops combining didactic and experiential learning over longer durations with supervision and feedback. Less sophisticated training was brief, involving lectures or seminars, with no supervision or feedback. Competency assessments and fidelity testing were underperformed. Conclusions: Training in some interventions might not have facilitated the implementation of skills or techniques to enable the paradigm shift and behavior change required for physical therapists to effectively deliver a biopsychosocial intervention. Lack of competency assessments and fidelity checking could have impacted the methodological quality of biopsychosocial interventions. Impact: This study highlighted problematic reporting, training, assessment of competency, and fidelity checking of physical therapist–delivered individualized biopsychosocial interventions. Findings here highlight why previous interventions could have shown small effect sizes and point to areas for improvement in future interventions. These findings can help inform future research and facilitate more widespread implementation of physical therapist–delivered biopsychosocial interventions for people with musculoskeletal pain and thereby improve their quality of life.